2021
DOI: 10.1111/jfpp.15788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrusion parameters on the physicochemical characteristics of extruded barley ready‐to‐eat snacks

Abstract: Cereal crops have been used extensively to feed ruminant and monogastric animals and serve as a primary energy source (Bdour et al., 2014). Barley, an ancient and important cereal, is the fifth most cultivated cereal in the world, accounting for ~9.4% of the world's total area for cereal production (Youssef et al., 2012). Barley is of particular interest in the production of functional foods owing to its high dietary fiber content. The presence of a number of bioactive components such as β-glucan and phenolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Extrusion puffing technology is one of the most widely used processing methods in the food industry due to its low processing cost compared to other cooking and processing methods ( 23 ). At the same time, black/purple rice is typically a better source of important phytochemicals, fiber, and minerals and has gained popularity due to various active ingredients that prevents most of the chronic diseases ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrusion puffing technology is one of the most widely used processing methods in the food industry due to its low processing cost compared to other cooking and processing methods ( 23 ). At the same time, black/purple rice is typically a better source of important phytochemicals, fiber, and minerals and has gained popularity due to various active ingredients that prevents most of the chronic diseases ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion puffing process is a highly-promising technique for the production of the rice and rice-based products, which greatly impacts the physicochemical properties of rice extrudates (2). In terms of physical properties of extrusion puffing, it has observed that the extrusion puffed sample has relatively lower radial expansion ratio (RER) value than that reported previously (23), which can be attributed to the higher screw rate accelerates the gelatinization of starch and may produce a higher pressure drop at the outlet of the die, thus promoting cell nucleation and expansion (16). Extrusion puffing led to black/purple rice have higher water absorption index (WAI) and water solubility index (WSI) values.…”
Section: Extrusion Puffing Enhanced Nutritional Values Of Black/purpl...mentioning
confidence: 96%
“…It is an efficient processing technique that produces foods with distinctive textural characteristics (Leonard et al, 2020). Extruders are single-or multiple-screw systems, with twin-screw systems being the most typical ones of BR into flour combination resulted in lower hardness of extrudates while producing ready-to-eat snacks (Chou & Hsu, 2021). BR is rich in fiber and bioactive phytochemicals, such as total phenolic content (TPC) and antioxidants, which have several health benefits, including the prevention of chronic illnesses and better glycemic control (Saleh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%